The students' habits of mind in biology learning animalia material - Lissa, Lissa; Subkhi, Nur; Hizbullatif, Akrom (Universitas Wiralodra, 2024)
This study aims to determine students’ habits of mind in learning biology Animalia material at Class X MIPA 5 SMAN 1 Indramayu. There is still little information about the habits of mind in biology learning that students currently have and habits of mind in biology learning are still less considered and developed. This research is a type of qualitative research. The subjects of this study were students in class X MIPA 5 SMAN I Indramayu consisting of 32 respondents, using a purposive sampling technique. The instruments used were habits of mind questionnaire sheet with a Likert scale measurement and a validated unstructured interview sheet. Habits of Mind in the study consisted of 12 indicators, adapted from Costa and Callik, and Marzano. It consists of primary data and secondary data. Data collection techniques were conducted by distributing questionnaires to students and filling out a list of interview questions. Data analysis has three stages: data reduction, data display, and conclusion drawing/verification. The Miles & Huberman model was used as a data analysis technique. This type of interactive model has three stages, namely: data reduction, data display, and conclusion drawing/verification. The results showed that students' habits of mind in class X MIPA 5 SMAN 1 Indramayu in learning biology material Animalia, in general, is included in the very good category with a percentage level of 85%. This means that students in class X MIPA 5 SMAN 1 Indramayu already have a very good habit of mind attitude in the biology learning process.